Key and checklist of Xanthophyllum (Polygalaceae) of Borneo - W.J.J.O. De Wilde; Brigitta E.E. Duyfjes (Reinwardtia, 2009)
A key to and a check list of the 56 Xanthophyllum (Polygalaceae) species of Borneo is presented. One species is newly described, X. albicaulis. Xanthophyllum hildebrandii is sunk in X. ellipticum.